Recognition and management of neonatal hemodynamic compromise - Tai-Wei Wu; Shahab Noori (Elsevier, 2021)
Hemodynamic compromise of the neonate can occur in various clinical situations, including but not limited to maladaptation during the early transitional period, sepsis, congenital heart anomalies, hemodynamically significant patent ductus arteriosus, persistent pulmonary hypertension of the newborn, systemic inflammatory diseases such as necrotizing enterocolitis, and dehydration. Despite the handful of advances in neonatal care through ground-breaking clinical trials, the management of neonatal shock is often dependent on the bedside clinician's experience and training without the aid of high-level evidence. However, the recognition for the importance of comprehensive and serial hemodynamic assessment is growing. There is now a wealth of literature investigating the use of functional echocardiography, near-infrared spectroscopy, and noninvasive impedance-based cardiometry to complement common bedside hemodynamic measures such as blood pressure and heart rate measurement. In this review article, the pathophysiology of neonatal hemodynamic compromise is outlined, and concomitant best-evidence management for hemodynamic compromise in the neonate is proposed.